URGENSI PENGADILAN HUBUNGAN INDUSTRIAL DALAM PENYELESAIAN SENGKETA HUKUM DALAM DUNIA INDUSTRI - Faridy, Faridy; Hindriyani, Lilin (Legal Studies Journal, 2023)
A dispute must be resolved peacefully and through negotiations between the two parties to the dispute. Settlement of Industrial Relations Disputes can be done through litigation or non-litigation. There are 4 ways to resolve industrial relations disputes that can be used using non-litigation channels, including bipartite, conciliation, arbitration and mediation. The dispute resolution process is not carried out before the court, however there are some who need the assistance of a neutral third person so that an agreement can be quickly reached between the worker/laborer and the entrepreneur and so that it does not harm either of them. The Industrial Relations Court is a dispute resolution model that must be resolved when a dispute is discovered between workers/laborers and employers. The Industrial Relations Court plays an important role in resolving labor disputes in Indonesia. Based on Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes, PHI has the authority to examine, adjudicate and decide cases related to labor disputes. PHI's role in resolving labor disputes includes resolving disputes regarding rights, resolving interest disputes, resolving employment termination (PHK) disputes and resolving disputes between worker/labor unions within a company. The Industrial Relations Court (PHI) is expected to be able to resolve labor disputes in Indonesia fairly, quickly and cheaply so as to create harmonious industrial relations between workers/laborers and employers